Ketepatan Menjelaskan Ruang Lingkup Pembelajaran Terkait Etika Dan Politik Pendidikan di MA Islamiyah Balen - Zahrotun Muchoiyaroh; Sri Minarti (Yayasan Al-Afif, 2026)
This study examines the accuracy of explaining the scope of learning related to educational ethics and politics. The problem addressed is the limited understanding of how educational ethics and politics are integrated and communicated within the learning process. The research aims to analyze the accuracy and comprehensiveness of explanations regarding the scope of educational ethics and politics in educational settings. Data were collected through literature review, document analysis, and observations of learning materials related to educational ethics and politics. The findings indicate that accurate explanations of the learning scope help learners understand ethical values, political dimensions of education, and their implications for educational practices. Furthermore, clear and comprehensive explanations improve critical thinking and awareness of educational issues. The study concludes that the accuracy of explaining the scope of educational ethics and politics is essential for supporting effective learning and fostering informed educational perspectives.